Mushroom-mediated biosynthesis of NPs: a green approach toward antimicrobial applications - Mohammed Al Qutaibi; Suresh R. Kagne; Abubakar Salam Bawazir; Barrawaz Aateka Yahya (CyTA - Journal of Food)
Nanotechnology has emerged as a promising field, but the conventional synthesis methods for nanoparticles (NPs) often involve toxic chemicals. Consequently, this has driven interest in green, eco-friendly biosynthesis approaches using biological entities like mushrooms. Mushrooms are rich in proteins, enzymes, and other biomolecules that can facilitate the bioreduction of metal ions into NPs. This review summarizes the mechanisms of mushroom-mediated biosynthesis of metallic NPs, including silver, gold, palladium, titanium, zinc, copper, and iron oxides. The unique properties of these biogenic NPs make them potential candidates for diverse applications, with a particular focus on their antimicrobial activities against various pathogens. The antimicrobial mechanisms involving cell damage, oxidative stress, and metal ion release are discussed. While highly promising, challenges remain regarding size/shape control, cytotoxicity, and optimization for large-scale production. However, mushroom-based green nanosynthesis offers a sustainable approach to developing effective antimicrobial agents by leveraging the reduction capabilities of fungal biomolecules. Biosynthesized NPs, especially silver NPs, have demonstrated significant antimicrobial activity against a wide range of pathogenic bacteria and fungi. The antimicrobial efficacy varies depending on the type of NPs, the mushroom species used, and the target microorganisms. The review highlights current progress and prospects in this rapidly evolving interdisciplinary field that combines biology and nanotechnology.